Policies, Programs, and Practices: Exploring the Complex Dynamics of Assessment Education in Teacher Education Across Four Countries - DeLuca, Christopher; Willis, Jill; Cowie, Bronwen; Harrison, Christine; Coombs, Andrew; Gibson, Andrew; Trask, Suzanne (Frontiers in Education, 2019)
There has been a global trend towards increased accountability and assessment in schools over the past several decades. Across policy and professional standards, teachers have been repeatedly called to integrate assessment throughout their practice to identify, monitor, support, evaluate, and report on student learning. This professional capacity to integrate and utilize assessment to effectively facilitate student learning has long been characterized as teachers’ ‘assessment literacy’, or more recently ‘assessment competency’ and ‘assessment capability’. Concerningly, research indicates that teachers generally maintain low levels of assessment knowledge and skills, with beginning teachers particularly underprepared for assessment in schools. This persistent finding is unsurprising as researchers argue that assessment has historically been a neglected area of study in teacher education programs. However, with the rise of accountability mandates, assessment is beginning to occupy a more prominent and necessary role in preservice preparatory programs. However, analysing and situating assessment education in relation to broader conceptions of assessment literacy remains necessary in order to effectively promote the assessment capability of beginning teachers. Likewise, understanding how assessment education and assessment literacy are shaped by the complex dynamics and larger teacher education frameworks and how they contribute to teachers’ developing professional identities is essential in constructing a more comprehensive view of teacher preparation within and for accountability-driven systems of education. This paper analyzes teacher education policies, programs, and practices aimed at supporting initial teacher learning in assessment across four country contexts: Australia, Canada, England, and New Zealand. Bernstein’s (1999) codes of classification and framing provide an analytic discourse for examining the vertical and horizontal messages about assessment that shape teacher capability in this key area of professional practice. In drawing on policy and teacher education documents and qualitative data (i.e., interview and teacher reflections) from across each country context, the paper concludes with five consistent and interconnected findings about the complex landscape for teacher preparation in assessment.